The Use of Think-Talk-Write (TTW) Learning Model to Improve Islamic Education Learning Outcomes on the Subject of Respecting and Loving Parents and Teachers - Mochammad Syafiuddin Shobirin; Chytia Tulusiawati (SCHOOLAR: Social and Literature Study in Education, 2022)
This research was carried out aiming to improve student learning outcomes using the Think-Talk-Write (TTW) learning model in Islamic Religious Education subjects on the subject of Respecting and Loving Parents and Teachers. Think-Talk-Write (TTW) learning model is a suitable learning model to improve student learning outcomes. This learning model applies important stages in the lesson, namely the Think, Talk, and Write stages. This research was conducted at the SMA Negeri Plandaan Jombang with 33 students as the research subjects, namely class IX IPS 2. This research used Classroom Action Research and could be completed in 2 cycles and 2 times doing tests.